709 Healthy Sleep as an important resource and buffer for intersectional discrimination: Results from Covid 19 study. (3rd May 2021) - Pandey, Abhishek; Littlewood, Kerry; Spadola, Christine; Rosenthal, Michelle; Cooper, Larry; Carter, Shima; Bennett, Russell; Hash, Jonika; Kirtman, Nissa; Ward, Teresa
Abstract: Introduction: Our previous studies have highlighted sleep disparities for this underserved population, including how Grandparents Raising Grandchildren (GRG) experience troubled and disruptive sleep. Intersectional types of discrimination facing these families during COVID 19, include: race/ethnicity of self and children, income, age, essential workforce status, and impairments (mobility, vision, and hearing). This current study intends to explore how healthy sleep is an important resource (potential buffer) for GRG experiencing intersectional discrimination during COVID 19. Methods: We used community partnerships to recruit 600 GRG from all fifty states in USA and several tribes to complete an online survey on their experiences with caregiving and intersectional discrimination during COVID 19. We developed an index on intersectional discrimination based on GRG lived experiences to inform the survey and used descriptive and bivariate statistics to profile this group. Chi-square Automatic Interaction Detector (CHAID) analysis was used to build a predictive model to help determine how variables in our study best merge to explain intersectional discrimination. Results: Of the GRGs', 37% were between 54–65 years and 33% cared for children 6 to 10 years for at least 5 years. The types of discrimination that were more likely to be included in intersectional discrimination include: Black or African American [83.8% (31)], my child's race [59.5% (22)], my lower economic status [56.8% (21)], and my status as a caregiver [56.8% (21)]. The resource needs that showed the most disparity (higher rate showed higher priority/extreme concern) between those with ID and those without included: Information on how COVID impacts race and ethnicity differently (6.0 vs. 3.61), ability to pay utilities (3.7 vs. 1.99), and information on how to achieve healthy sleep (4.19 vs. 2.64). Conclusion: This study suggests that GRG facing intersectional discrimination identify the importance of attaining information on how to achieve healthy sleep as an important resource to them during COVID 19. These results can be used to help mobilize resources and disseminate information for this underserved group to improve healthy sleep and also model for their extended families and communities. Support (if any): This study was conducted by the Grandfamilies Outcome Workgroup, (GrOW), with support from Generations United and Collaborative Solutions.